Application of Geographic Information System (GIS) and Comparison of Active Substances in Medicinal Plants Used in Malaria Treatment Based on Folk Medicine Wisdom in Sa Kaeo Province - sinwat, Suratsawadee; Sirisa-ard, Panee; Nithikathkul, Choosak (International Journal of Innovative Research in Medical Science, 2024)
Introduction: Malaria is a tropical disease caused by Plasmodium parasites. The parasite spreads to people through the bite of infected female Anopheles mosquitoes. Malaria occurs mainly in poor, tropical, and subtropical areas of the world. The use of traditional medicine/traditional healers is prominent among populations in low-income countries with malaria infection. This study investigated the use of medicinal plants in the treatment of malaria by traditional healers. As well as studying the chemicals in medicinal plants used in treating malaria. To develop information on traditional medicinal plants used to treat and prevent malaria. Methodology: In-depth interviews were conducted along with observational studies of traditional healers. Results: The results showed that 13 medicinal plants have been used in the treatment of malaria by the folk healers in the study areas. The medicinal plants most common used by folk healers are neem (Azadirachta indica A.Juss.), quinine (Brucea javanica (L.) Merr.), wormwood (Tinospora crispa (L.)), and Eurycoma longifolia Jack. These main medicinal plants have the nourishing, therapeutic and preventive properties for malaria during a journey in the forest. They have been used as analgesic against all kinds of fever such as persistent fever and malaria. Each folk healer has been taught by their ancestors with at least 15 years of experience in healing and taking care of a large number of patients in their community. As these 2 provinces are adjacent to Cambodia, all folk healers can treat malaria even in severe stages such as cerebral malaria, malaria-induced splenic infarction and other similar fever conditions. Conclusion: The active substances or phytochemicals of 5 medicinal plants used in the treatment of malaria were characterized using crude ethanol extracts. Two primary phytochemicals were identified in Azadirachta indica A.Juss. and Ficus Racemosa Linn. which were terpenoids and phenolics, two phytochemicals were identified in Brucea javanica (L.) Merr. which were alkaloids and phenolics while three phytochemicals were identified in Tinospora crispa (L.) and Eurycoma longifolia Jack which were terpenoids, alkaloids and phenolics. For the total alkaloid content in 3 medicinal plants, Brucea javanica (L.) Merr. had highest total alkaloid content of 1.73-1.84%, followed by Tinospora crispa (L.) 1.15-1.59% and Eurycoma longifolia Jack 0.34-0.58%. In conclusion, folk healers in Sa Kaeo Province used medicinal plants gathered from their local community forests, which are found in every district, according to a study on the distribution and density of medicinal plants used in the treatment and prevention of malaria in the province's various districts. These therapeutic plants' coordinates were found using the geographic information system (GIS).